Interlocking Membrane/Catalyst Layer Interface for High Mechanical Robustness of Hydrocarbon‐Membrane‐Based Polymer Electrolyte Membrane Fuel Cells. (27th March 2015) - Oh, Keun‐Hwan; Kang, Hong Suk; Choo, Min‐Ju; Jang, Duk‐Hun; Lee, Dongyoung; Lee, Dai Gil; Kim, Tae‐Ho; Hong, Young Taik; Park, Jung‐Ki; Kim, Hee‐Tak
<x xml:space="preserve">Abstract</x> A physical interlocking interface that can tightly bind a sulfonated poly(arylene ether sulfone) (SPAES) membrane and a Nafion catalyst layer in polymer electrolyte fuel cells is demonstrated. Owing to higher expansion with hydration for SPAES than for Nafion, a strong normal force is generated at the interface of a SPAES pillar and a Nafion hole, resulting in an 8‐fold increase of the interfacial bonding strength at RH 50% and a 4.7‐times increase of the wet/dry cycling durability.